An interesting new species of Nososticta Hagen from southern New Guinea (Odonata, Disparoneuridae) - Michalski, John; Richards, Stephen; Theischinger, Gunther (Zootaxa, 2012)
Nososticta acuminata, a new disparoneurid damselfly from the Lakekamu Basin in Gulf Province of Papua New Guinea, is described. It is most similar to N. smilodon Theischinger & Richards, but the male has uniquely pointed superior anal appendages.